2007
DOI: 10.1164/rccm.200702-326oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1-Year Treatment with Cyclophosphamide on Outcomes at 2 Years in Scleroderma Lung Disease

Abstract: Rationale: The Scleroderma Lung Study enrolled 158 patients with scleroderma-related interstitial lung disease in a placebo-controlled trial of oral cyclophosphamide (CYC). Although treatment-related benefits in pulmonary function, skin scores, and patient-centered outcomes were demonstrated after 1 year of therapy, the duration of benefit beyond 1 year was unclear. Objectives: A second year of follow-up was performed to determine if these effects persisted after stopping treatment. Methods: A detailed analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
259
1
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 415 publications
(278 citation statements)
references
References 31 publications
4
259
1
14
Order By: Relevance
“…A recent placebo-controlled, double-blind study showed a statistically significant but modest (2.53%) beneficial effect of oral cyclophosphamide on lung function, as measured by forced vital capacity (FVC) (3). This small effect was not persistent at 1 year of followup (4), although the patients who had received cyclophosphamide still demonstrated a benefit in the dyspnea score.…”
mentioning
confidence: 99%
“…A recent placebo-controlled, double-blind study showed a statistically significant but modest (2.53%) beneficial effect of oral cyclophosphamide on lung function, as measured by forced vital capacity (FVC) (3). This small effect was not persistent at 1 year of followup (4), although the patients who had received cyclophosphamide still demonstrated a benefit in the dyspnea score.…”
mentioning
confidence: 99%
“…All patients fulfilled the 2013 classification criteria (van den Hoogen et al 2013). The follow-up period was defined as the time from the initial manifestation of SSc-related symptoms to either the date of death or the latest visit to our hospital.…”
Section: Methodsmentioning
confidence: 99%
“…However, no agents have been proven to effectively control ILD . Cyclophosphamide was demonstrated to stabilize lung function in a randomized controlled trial, but its beneficial effect disappeared at 24 months (Tashkin et al 2006;Tashkin et al 2007). Moreover, acute exacerbation of ILD (AE-ILD) occurs at a 1-year frequency of 1.25%-3.3% and at a lifetime incidence of 7.2%, with a high mortality rate in patients with connective tissue disease (Park et al 2007;Suda et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At present, only daily oral or pulse intravenous cyclophosphamide (CYC) have been shown in large randomized, doubleblinded, placebo-controlled trials to alter the course of SSc-ILD (2)(3). While highlighting that SSc-ILD is treatable, the overall magnitude of the response to CYC in these studies was modest and the beneficial effects appeared to fade within a year after stopping treatment (2)(3)(4). When these features are combined with the potential toxicity associated with CYC (5), there has been considerable controversy about whether all patients with SSc-ILD should be treated or whether therapy should be reserved for patients at the greatest risk for progression or deterioration (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%